Prevalence and incidence of pre‐diabetes and diabetes mellitus among people living with HIV in Ghana: Evidence from the EVERLAST Study. Issue 4 (10th November 2020) - Sarfo, Fred Stephen; Norman, Betty; Nichols, Michelle; Appiah, Lambert; Osei Assibey, Shadrack; Tagge, Raelle; Ovbiagele, Bruce
Abstract : Background: Available data from high‐income countries suggest that people living with HIV (PLWH) have a four‐fold higher risk of diabetes compared with HIV‐negative people. In sub‐Saharan Africa, with 80% of the global burden of HIV, there is a relative paucity of data on the burden and determinants of prevalent and incident dysglycaemia. Objectives: To assess the prevalence and incidence of pre‐diabetes (pre‐DM) and overt diabetes mellitus (DM) among PLWH in a Ghanaian tertiary medical centre. Methods: We first performed a cross‐sectional comparative analytical study involving PLWH on combination antiretroviral therapy (cART) ( n  = 258), PLWH not on cART ( n  = 244) and HIV‐negative individuals ( n  = 242). Diabetes, pre‐DM and normoglycaemia were defined as haemoglobin A1C (HBA1c) > 6.5%, in the range 5.7–6.4% and < 5.7% respectively. We then prospectively followed up the PLWH for 12 months to assess rates of new‐onset DM, and composite of new‐onset DM and pre‐DM. Multivariate logistic regression models were fitted to identify factors associated with dysglycaemia among PLWH. Results: The frequencies of DM among PLWH on cART, PLWH not on cART and HIV‐negative individuals were 7.4%, 6.6% and 7.4% ( P  = 0.91), respectively, while pre‐DM prevalence rates were 13.2%, 27.9% and 27.3%, respectively ( P  < 0.0001). Prevalent DM was independently associated with increasing age [adjusted odds ratio (95% confidence interval) (aOR, 95% CI) = 1.82 (1.20–2.77) for each 10‐year rise], male sex [aOR = 2.64 (1.20–5.80)] and log(triglyceride/HDL cholesterol) [aOR = 8.54 (2.53–28.83)]. Prevalent pre‐DM was independently associated with being on cART [aOR (95% CI) = 0.35 (0.18–0.69)]. There were a total of 12 cases of incident DM over 359.25 person‐years, giving 33.4/1000 person‐years of follow‐up (PYFU) (95% CI: 18.1–56.8/1000), and an rate of incident pre‐DM of 212.7/1000 PYFU (95 CI: 164.5–270.9/1000). The two independent factors associated with new‐onset DM were having pre‐DM at enrolment [aOR = 6.27 (1.89–20.81)] and being established on cART at enrolment [aOR = 12.02 (1.48–97.70)]. Conclusions: Incidence rates of pre‐DM and overt DM among Ghanaian PLWH on cART ranks among the highest in the literature. There is an urgent need for routine screening and a multidisciplinary approach to cardiovascular disease risk reduction among PLWH to reduce morbidity and mortality from the detrimental effects of dysglycaemia.